Resolving the status of Pyriporoides and Daisyella (Bryozoa: Cheilostomata), with the systematics of some additional taxa of Calloporoidea having an ooecial heterozooid - Gordon, Dennis P.; Taylor, Paul D. (Zootaxa, 2017)
Based on the examination of type and newly discovered specimens, the scope of the calloporid genus Pyriporoides Hayward & Thorpe, 1989 is expanded to include Daisyella Gordon, 1989. All species of Pyriporoides have colonies of branching uniserial runners and acleithral ovicells that are borne on and/or develop concurrently with a distal heterozooid, not the distal autozooid. The ooecial heterozooid is usually kenozooidal but can be avicularian. Correlated characters include, inter alia: a raised granular rim that encloses a generally well-developed cryptocystal shelf, and a longitudinally elongate opesia that may be constricted and asymmetrical. Articulated perioral/pericryptocystal spines are present as well as occasional accessory spines borne on the lateral gymnocyst. Pyriporoides is mostly austral in distribution, ranging from the southern Indian Ocean and New Zealand’s subantarctic islands to West Antarctica, with an outlier in the northeast Atlantic. Three additional genera, one little known, two new to science, have species with small, mostly spot-like, colonies that share most of the zooidal characters of Pyriporoides and so are described and discussed in this context. These genera are Apiophragma Hayward & Ryland, 1993, Olisthella n. gen. and Bryobrownius n. gen. A cladistic analysis of the taxa described herein plus selected outgroup species of Calloporidae and Pyrisinellidae identified an apparent clade within or derived from Calloporidae, the significance of which is discussed.